PENGARUH JOB EMBEDDEDNESS DAN WORK FAMILY CONFLICT TERHADAP TURNOVER INTENTION DAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI PADA PT. BANK NEGARA INDONESIA - Noviasta, Tata; Ritonga, Ilham Mubaraq; Pentana, Sopi (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to determine the effect of job embeddedness and work family conflict on turnover intention at PT. Bank Negara Indonesia Medan which is moderated by organizational commitment partially. The design of this study is multiple linear regression analysis and MRA is used as an analysis tool to determine how the influence of independent variables on the moderated dependent variable. This study uses an associative research type with a quantitative approach. The population and sample used in this study were 170 employees. The results of this study indicate that the significance variable of job embeddedness is 0.035 <0.05, this indicates that job embeddedness has a significant effect on turnover intention, so accept Ha and reject H0. From the t count obtained 6.034 and t table 1.974, which means that the job embeddedness variable has a positive effect on turnover intention. The significance of work family conflict is 0.000 <0.05, this shows that work family conflict has a significant effect on turnover intention, so accept Ha and reject H0. From tcount obtained 2.127 and ttable 1.974, which means that the work family conflict variable has a positive effect on turnover intention. Organizational commitment moderates the relationship between job embeddedness and turnover intention. Organizational commitment moderates the relationship between work family conflict and turnover intention.